Lycium barbarum Polysaccharides as Antibiotic Substitutes Improve Growth Performance, Serum Immunity, Antioxidant Status, and Intestinal Health for Weaned Piglets - Yin, Yexin; Wang, Fang; Yang, Mei; Tan, Bie; Yin, Yulong; Chen, Jiashun; Yang, Zhe (Frontiers in Microbiology, 2022)
The aim of the present study is to investigate the effects of dietary Lycium barbarum polysaccharides (LBPs) supplementation on the growth performance, immune response, serum antioxidant status, and intestinal health of weaned piglets. In total, 24 crossed healthy weaned piglets [Duroc × (Yorkshire × Landrace)], of similar body weight (body weight = 7.47 ± 0.22 kg), were randomly allocated to three treatment groups: CON (basal diet); LBPs (basal diet plus 4000 mg/kg LBPs); and ABO (basal diet plus 20 mg/kg flavomycin & 50 mg/kg quinocetone). There were eight replicates per group and one piglet per replicate. The study lasted 28 days. When compared with CON, LBPs or ABO dietary supplementation increased average daily gain (P < 0.05), decreased the ratio of feed to gain, and the diarrhea ratio (P < 0.05). Similarly, when compared with CON, LBPs dietary supplementation increased serum immunoglobulin G, immunoglobulin M, interleukin-10, interleukin-2, and tumor necrosis factor-α levels (P < 0.05). Dietary LBPs enhanced the activity of serum total antioxidant capacity and glutathione peroxidase, and decreased malondialdehyde levels (P < 0.05). Principal component analysis showed a distinct separation between CON and LBPs groups, but no differences between ABO and LBPs groups. LBPs addition increased Lactobacillus and Faecalibacterium (P < 0.05) levels, while it decreased Enterococcaceae and Enterobacteriaceae (P < 0.05) levels. Furthermore, when compared with the CON group, LBPs increased villus height (P < 0.05) and the villus height to crypt depth ratio in the duodenum and jejunum (P < 0.05). Thus, dietary supplementation with LBPs improved growth performance, antioxidant capacity and immunity, regulated intestinal microbial composition, and may be used as an efficient antibiotic alternative in weaned piglet feed.